THE RELATIONSHIP BETWEEN VITAMIN D DEFICIENCY AND THE SEVERITY OF COVID-19 - Persson Jeffry, Erick (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The global health issue known as the COVID-19 pandemic, resulting from the SARS-CoV-2 virus, has prompted extensive research into factors affecting the severity of the disease. Among these factors, the connection between vitamin D levels and the outcomes of COVID-19 has become an increasingly intriguing field of study.Vitamin D is a fat-soluble vitamin renowned for its importance in bone health and immune system regulation. According to the latest studies, inadequate levels of vitamin D might be linked to a higher susceptibility to various respiratory infections. As a result, researchers are investigating the potential impact of vitamin D on the severity of COVID-19.Multiple observational investigations have found a link among a lack of vitamin D and a higher vulnerability to respiratory infections such as COVID-19. Some studies have revealed that individuals with inadequate vitamin D levels had more severe COVID-19 symptoms, greater rates of admission to the hospital, and a greater mortality rate than those with adequate vitamin D levels. Vitamin D is thought to help regulate the immune response by influencing both the adaptive as well as the innate immune systems. Deficiency may affect immunological function, resulting in an altered antiviral response and increased inflammation, which may contribute to the development of COVID-19.It is crucial to emphasize, however, that the existing research on the connection with insufficient vitamin D levels and the severity of COVID-19 are continuously evolving, with contradicting findings reported. There are significant constraints to the extant research, particularly differences in study methodologies, sample sizes, also populations investigated. Furthermore, it remains uncertain whether there is a cause-and-effect relationship between vitamin D deficiency and COVID-19 severity, as the observed relationships might be impacted by other confounding variables. Given vitamin D's possible involvement in immune function and the existing data linking it to COVID-19 severity, further well-designed research, particularly randomized controlled trials, are needed to demonstrate a causal relationship.